Human stem cell–derived neurons and astrocytes to detect novel auto-reactive IgG response in immune-mediated neurological diseases - Mathias, Amandine; Perriot, Sylvain; Jones, Samuel; Canales, Mathieu; Bernard-Valnet, Raphaël; Gimenez, Marie; Torcida, Nathan; Oberholster, Larise; Hottinger, Andreas F.; Zekeridou, Anastasia; Theaudin, Marie; Pot, Caroline; et al. (Frontiers in Immunology, 2024)
Background and objectives: Up to 46% of patients with presumed autoimmune limbic encephalitis are seronegative for all currently known CNS antigens. We developed a cell-based assay (CBA) to screen for novel neural antibodies in serum and CSF using neurons and astrocytes derived from human induced pluripotent stem cells (hiPSC).Methods: Human iPSC-derived astrocytes or neurons were incubated with serum/CSF from 99 patients (42 with inflammatory neurological diseases (IND) and 57 with non-IND (NIND)). The IND group included 11 patients with previously established neural antibodies, six with seronegative neuromyelitis optica spectrum disorder (NMOSD), 12 with suspected autoimmune encephalitis/paraneoplastic syndrome (AIE/PNS), and 13 with other IND (OIND). IgG binding to fixed CNS cells was detected using fluorescently-labelled antibodies and analyzed through automated fluorescence measures. IgG neuronal/astrocyte reactivity was further analyzed by flow cytometry. Peripheral blood mononuclear cells (PBMC) were used as CNS-irrelevant control target cells. Reactivity profile was defined as positive using a Robust regression and Outlier removal test with a false discovery rate at 10% following each individual readout.Results: Using our CBA, we detected antibodies recognizing hiPSC-derived neural cells in 19/99 subjects. Antibodies bound specifically to astrocytes in nine cases, to neurons in eight cases and to both cell types in two cases, as confirmed by microscopy single-cell analyses. Highlighting the significance of our comprehensive 96-well CBA assay, neural-specific antibody binding was more frequent in IND (15/42) than in NIND patients (4/57) (Fisher test, p=0.0005). Two out of four AQP4+ NMO , and 4/7 definite AIE/PNS with intracellular-reactive antibodies (1 GFAP astrocytopathy, 2 Hu+, 1 Ri+ AIE/PNS)), as identified in diagnostic laboratories, were also positive with our CBA. Most interestingly, we showed antibody-reactivity in 2/6 seronegative NMOSD, 6/12 probable AIE/PNS, and 1/13 OIND. Flow cytometry using hiPSC-derived CNS cells or PBMC detected antibody binding in 13 versus 0 patients, respectively, establishing the specificity of the detected antibodies for neural tissue.Our unique hiPSC-based CBA allows for the testing of novel neuron-/astrocyte-reactive antibodies in patients with suspected immune-mediated neurological syndromes, and negative testing in established routine laboratories, opening new perspectives in establishing diagnosis of such complex diseases.